2010
DOI: 10.1177/0267658310365768
|View full text |Cite
|
Sign up to set email alerts
|

Dominant language transfer in adult second language learners and heritage speakers

Abstract: The effects of language transfer have been amply documented in second language (L2) acquisition and, to a lesser extent, in the language contact/loss literature (Cook, 2003). In both cases, the stronger and often dominant language encroaches into the structure of the less dominant language in systematic ways. But are transfer effects in these two situations comparable: is first language (L1) influence in adult L2 learners similar to L2 influence in the L1 of early bilinguals? The current study addresses this q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(128 citation statements)
references
References 54 publications
7
106
1
Order By: Relevance
“…Much research has attested divergent behavior by heritage speakers in several domains of language, especially in phenomena located at the linguistic interfaces, and in particular the syntax-pragmatics interface (Montrul 2004(Montrul , 2010. Interface phenomena are notoriously problematic, not only for heritage speakers, but for all types of bilingual speakers, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Much research has attested divergent behavior by heritage speakers in several domains of language, especially in phenomena located at the linguistic interfaces, and in particular the syntax-pragmatics interface (Montrul 2004(Montrul , 2010. Interface phenomena are notoriously problematic, not only for heritage speakers, but for all types of bilingual speakers, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…IoninandZubizarreta(2010, in an introductory paper to selected articles discussing the issue of L1 transfer at the linguistic interfaces, point out that these articles provided evidence for the following claims. L1 knowledge of structures at both external and internal interfaces is subject to transfer more than knowledge of purely syntactic structures (see, Montrul, 2010). Also, it is possible to recover from negative transfer of knowledge of at least structures at the syntax-semantics interface (see, Oh, 2010).…”
Section: Acquisition Of Modern Standard Arabic Alresainimentioning
confidence: 99%
“…This also leads to the conclusion that despite the fact that exposure to MSA was almost limited to the written form for the late acquirers, the required MSA input for restructuring L1 knowledge of the syntactic phenomena under study must have been adequately available to these participants together with their full access to UG. Montrul(2010) claims that L1 knowledge of structures at both internal and external linguistic domain interfaces is subject to transfer more than L1 knowledge of purely syntactic structures. This claim places further emphasis on the assumption here that the participants with late AoE had at least transferred their L1 knowledge of resumption in object relative clauses when they started acquiring MSA, but they also managed to restructure this knowledge to a uniform representation of MSA.…”
Section: The Effect Of the Colloquial Dialects (The L1s)mentioning
confidence: 99%
“…Montrul (2010a) cites various studies that suggest that heritage speakers are outperformed by native speakers in a variety of grammatical measures. Montrul (2010a) notes that heritage speakers of Spanish perform worse than their monolingual counterparts in gender marking (Montrul, Foote, & Perpiñán 2008), the subjunctive mood (Silva-Corvalán, 1994), usage of the dative preposition "a" (Montrul & Bowles, 2009), and differential object marking (Montrul, 2010b). SilvaCorvalán (1991SilvaCorvalán ( , 1994 has shown that HS suffer considerable L1 attrition, in part caused by the contact situation between their L1 and the majority language, English.…”
Section: Motivation For Study and Research Questionsmentioning
confidence: 99%